A Study of Network Negative News Based on Behavioral Finance Analysis of Abnormal Fluctuation of Stock Price - Cheng Chung Wu; Ye Yan; Tiantong Yuan; Chih Chiang Huang; Ya Ju Tsai (Discrete Dynamics in Nature and Society)
This article studies the model of the impact of real negative news on stock prices and provides evidence using China’s A-share listed companies as an example. It first defines the negative news of the network. Then, it constructs the negative news to the stock price influence model, from the perspective of the theory of behavioral finance, the relationship between stock market and investor sentiment is systematically analyzed, and the theoretical support for the research of this paper is provided according to the definition of network negative news concept using the event study, abnormal returns test, regression analysis of the sample selected out of the study, observation of negative news before and after the abnormal returns, and excess returns changes. Studies have shown that negative news before 1 day and after 4 days makes stock price volatility larger, resulting in excess returns. The network negative news on the listed company’s stock price fluctuations can cause a certain degree of impact; in the short term, the fluctuation of the stock price of listed companies is more active. This article finds that when online media disclose negative information on listed companies from one day before to four days later, stock prices will fluctuate greatly, generate excess returns, and continue to make stock fluctuations more active in the short term. In addition, when studying the influencing factors of the stock price fluctuations of listed companies, we found that stock price fluctuations are affected by the company’s performance. The better the company’s performance is, the smaller the stock price fluctuations will be when it is affected by negative news. Finally, we find that the higher the shareholding ratio of institutional investors in listed companies, the more stable the stock price.